Web services on deeply embedded devices with real-time processing - Moritz, G.; Pruter, S.; Timmermann, D.; Golatowski, F. (2008 IEEE International Conference on Emerging Technologies and Factory Automation, 2008)
Service-oriented architectures become more and more important in connecting devices with each other. The main advantages of service-oriented architectures are higher abstraction level and interoperability of devices. In this field Web services become the most important standard for communication between devices. But this upcoming technology is only available on powerful devices. Embedded hardware is often excluded from the deployment of Web services because of the lack of resources like computing power and memory. In this area also real-time capabilities for process control are required. This paper presents a new approach to handle Web services communication on deeply embedded hardware with the devices profile for Web services specification.